Associations of health disparities and physical activity with children's health and academic problems - Xiangrong Shi; Larry Tubb; Shande Chen; Kimberly G. Fulda; Susan Franks; Rustin Reeves; George Lister (Elsevier, 2014)
This study was aimed at examining the associations between health disparities and physical activity, and their contributions to health and academic problems in schoolchildren. Pertinent data from a community-wide survey were analyzed, which included 2930 households with schoolchildren aged 7-14 years. Associations between the parents' self-reported race/ethnicity, parental education, household income, children's health status, physical activity, and academic problems were determined by Chi-square and logistic regression analyses. Contributory factors for children's health status, physical activity, and academic problems were predicted by logistic regression fitting. Within white/Caucasian children, 86.0% had very good/excellent health and 77.9% were physically active, values higher than those in Latino/Hispanic (77.8%, p < 0.0001 and 71.9%, p = 0.0030) and black/African American children (80.0%, p = 0.0409 and 73.1%, p = 0.0973). White schoolchildren were less likely to have academic problems (8.9%) than Latino (12.5%, p = 0.0256) or black (26.1%, p < 0.0001) schoolchildren. Health status was reciprocally (p < 0.0001) inter-related to physical activity and was the most significant factor (p < 0.0001) associated with academic problems. Children's health status determined by both healthy lifestyles and sociodemographic factors is the most significant contributory factor associated with academic problems. Physical activity should be considered as an intervention to reduce health disparities and academic problems among schoolchildren.